Executive Law Review in an Effort to Accelerate Program Ease of Doing Business - Johannes Ibrahim Kosasih (Fakultas Hukum, Universitas Warmadewa, 2020)
Indonesia is currently still ranked below in attracting domestic and foreign investment because the existing regulations are not conducive. Many contributing factors, including central government regulations that are inconsistent in their implementation in the regions and the linkages of various regulations that support investment (for example: employment, land, credit, contracts, taxation, cross-country trade, business entities, bankruptcy and etc.), updates adapted to the era of free trade and fair business competition. One of the Government's efforts to improve the investment climate is to implement the Ease of Doing Business program that has been carried out by other countries in various parts of the world. This study aims to carry out the executive law review in an effort to accelerate program ease of doing. This study uses normative juridical research methods by examining various regulations and policies of the Central Government and local governments with a statute approach. The results of this study shows that there are three policies from the Government in the form of revoked, amended or maintained by the regulations referred to in 5 (five) dimensions in the evaluation of regulations, namely the accuracy of the type of legislation, the potential for disharmony in regulations, clarity of the formulation of regulations, assessment of conformity of norms, and effectiveness implementing statutory arrangements. These five dimensions in the Ease of Doing Business program are expected to provide synergy from existing regulations so that foreign investors can look at Indonesia as a country that is comfortable in investing and can provide benefits for businesses that are invested in Indonesia.